2020
DOI: 10.1093/femsle/fnaa081
|View full text |Cite
|
Sign up to set email alerts
|

High-added value products from microalgae and prospects of aquaculture wastewaters as microalgae growth media

Abstract: Aquaculture plays an important role in human nutrition and economic development but is often expanded to the detriment of the natural environment. Several research projects, aimed at cultivating microalgae in aquaculture wastewaters (AWWs) to reduce organic loads and minerals, along with the production of microalgal cell mass and metabolic products, are underway. Microalgal cell mass is of high nutritional value and is regarded as a candidate to replace, partially at least, the fish meal in the fish feed. Also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 138 publications
0
14
0
2
Order By: Relevance
“…Therefore, other microorganisms known for producing polyunsaturated fatty acids (PUFAs) such as microalgae and fungi could be employed in RAS-PHB and serve as a feed supplement. PUFAs, particularly eicosapentaenoic and docosahexaenoic acids, are known to be essential supplements in the aquaculture feed as they can improve fish health and the quality of seafood produced (e.g., increased omega-3 content in the seafood). ,, In this context, our proposed RAS-PHB system is still an optimal technology as the system can be further expanded and generalized for cultivating other microbial biomasses such as PUFA-producing microalgae under mixotrophic conditions (i.e., autotrophic and heterotrophic). ,, Previous studies have reported successful cultivations of different PUFA-rich microalgal strains using fish farm effluents under nonsterile conditions. , However, such an approach was limited by the low lipid content (25%) and low biomass yields (usually <400–850 mg/L) in the cultivated PUFA-producing microorganisms. , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, other microorganisms known for producing polyunsaturated fatty acids (PUFAs) such as microalgae and fungi could be employed in RAS-PHB and serve as a feed supplement. PUFAs, particularly eicosapentaenoic and docosahexaenoic acids, are known to be essential supplements in the aquaculture feed as they can improve fish health and the quality of seafood produced (e.g., increased omega-3 content in the seafood). ,, In this context, our proposed RAS-PHB system is still an optimal technology as the system can be further expanded and generalized for cultivating other microbial biomasses such as PUFA-producing microalgae under mixotrophic conditions (i.e., autotrophic and heterotrophic). ,, Previous studies have reported successful cultivations of different PUFA-rich microalgal strains using fish farm effluents under nonsterile conditions. , However, such an approach was limited by the low lipid content (25%) and low biomass yields (usually <400–850 mg/L) in the cultivated PUFA-producing microorganisms. , …”
Section: Resultsmentioning
confidence: 99%
“…25,74,75 In this context, our proposed RAS-PHB system is still an optimal technology as the system can be further expanded and generalized for cultivating other microbial biomasses such as PUFA-producing microalgae under mixotrophic conditions (i.e., autotrophic and heterotrophic). 71,76,77 Previous studies have reported successful cultivations of different PUFA-rich microalgal strains using fish farm effluents under nonsterile conditions. 75,76 However, such an approach was limited by the low lipid content (25%) and low biomass yields (usually <400−850 mg/L) in the cultivated PUFA-producing microorganisms.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…• Nannochloropsis sp. : that demonstrates a considerable fatty acid profile especially when using magnetic harvesting (Savvidou et al, 2020) and when it is cultivated in aquaculture wastewaters (Ansari et al, 2017;Dourou et al, 2020).…”
Section: Logical Architecture Of the System And Case Studymentioning
confidence: 99%
“…Improving the growth rate and feed conversion rate of fish is essential for the sustainable development of aquaculture (1,2). Amino acids play important roles in the nutrient metabolism of cultured fishes.…”
Section: Introductionmentioning
confidence: 99%